Intensive Writing Instruction by using Padlet Application in Indraprasta University PGRI - Andri Purwanto (International Journal of Education, Information Technology, and Others, 2020)
In the digital age the majority of students are already using gadgets in their daily lives. The development of increasingly sophisticated digital technology in this era presents its own challenges for Intensive Writing lecturer to continue to innovate and be creative in developing effective and interesting Intensive Writing teaching materials. However, after we pay attention in several universities most of the lecturers still do not use interesting and up-to-date teaching materials. Hence students are not excited and do not pay attention to the lesson enthusiastically. The result will affect their low interest and ability to learn English, especially writing. Therefore, it takes Intensive Writing Instruction by using the Padlet application. Padlet application is a digital media which is intended for instructional learning. This study aims to explain the use of Padlet application in the Intensive Writing instruction process in tertiary institutions. Data collection method is carried out by observation, interview and documentation. The results show that the use of the Padlet application can support lecturers in fun English learning activities. Because lecturers and students can write anything related to learning and exchange ideas by sending pictures, videos and links through Padlet application. They interact through digital technology with Padlet application so they no longer need a blackboard to write.